Managing with people in mind - Harvard Buisness Review (Harvard Business Review, Boston, US, 1991)
Considers people management from various angles. Looks at the managers' role; effective daily management; people and organizations; and solving managerial dilemmas.
Keywords: Management; Business Management; Management Techniques